Impact of knowledge oriented leadership on knowledge management processes in the Middle Eastern audit and consulting companies - Raudeliūnienė, Jurgita; Kordab, Mirna (Business, Management and Economics Engineering, 2019)
Purpose – this article aims to evaluate the influence of knowledge oriented leadership on knowledge management processes and the influence of those processes on the performance of the Middle Eastern audit and consulting companies.Research methodology – analysis of scientific literature, structural equation modelling and expert evaluation (structured questionnaire) were used in order to create hypotheses and research model, to collect data from the audit and consulting companies’ experts and to test research model and related hypotheses.Findings – the results of this research supported eight out of ten suggested hypotheses. Empirical evidence shows that leadership has a positive impact on knowledge acquisition, storage, and sharing processes in the Middle Eastern audit and consulting companies and knowledge management processes (creation, acquisition, sharing, storage and application) have positive influence on organizational performance.Research limitations – conducting the research in the Middle Eastern audit and consulting companies limits the possibility of generalizing the results to other types of businesses sectors as well as other geographical areas.Practical implications – conducted research results have practical value for audit and consulting companies as this study analyses the concept of knowledge oriented leadership and its impact on knowledge management processes and organizational performance.Originality/Value – this research investigated one of rare studies in the Middle East business sector, where the audit and consulting companies’ performance affected by the knowledge management processes was assessed considering knowledge oriented leadership as an influential factor that affects the knowledge management processes implementation.